1975
DOI: 10.1172/jci107963
|View full text |Cite
|
Sign up to set email alerts
|

Catalase, superoxide dismutase, and virulence of Staphylococcus aureus. In vitro and in vivo studies with emphasis on staphylococcal--leukocyte interaction.

Abstract: A B S T R A C T Since oxygen-free polymorphonuclear neutrophils (PMN) cannot kill Staphylococcus aureus normally, the usual mechanisms for PMN bactericidal activity probably involve hydrogen peroxide or superoxide. Catalase can destroy hydrogen peroxide, and superoxide dismutase breaks down superoxide. Experiments were performed to study the influence of these enzymes (which are found in staphylococci) on virulence for mice or on leukocyte-bacterial interaction. 15 staphylococcal strains were injected i.p. int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
152
0
6

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(163 citation statements)
references
References 20 publications
5
152
0
6
Order By: Relevance
“…KatA was described as a major virulence determinant in S. aureus, but studies with a catalase mutant revealed no difference in virulence in a murine abscess model of infection (34,18). We have shown compensatory expression and activity of AhpC in the absence of KatA.…”
Section: Vol 189 2007 Peroxide Stress Resistance Proteins Of S Aurmentioning
confidence: 67%
See 1 more Smart Citation
“…KatA was described as a major virulence determinant in S. aureus, but studies with a catalase mutant revealed no difference in virulence in a murine abscess model of infection (34,18). We have shown compensatory expression and activity of AhpC in the absence of KatA.…”
Section: Vol 189 2007 Peroxide Stress Resistance Proteins Of S Aurmentioning
confidence: 67%
“…Thus, scavenging of H 2 O 2 is important for aerobic survival. Catalase (KatA) is known to detoxify H 2 O 2 and was proposed to be a major virulence determinant in Staphylococcus aureus (34), where strains producing low levels of KatA were more sensitive to killing by neutrophils. However, a katA mutant of S. aureus was not attenuated in a murine-abscess model of infection (17).…”
mentioning
confidence: 99%
“…Catalase has traditionally been implicated as a virulence determinant in S. aureus (Kanafani & Martin, 1985;Mandell, 1975). However, recent studies with S. aureus katA mutants have revealed no differences in virulence from the corresponding wild-type strains in murine models of infection (Cosgrove et al, 2007;Horsburgh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this enzyme has been demonstrated to be an essential factor for the intracellular survival of bacteria such as Mycobacterium tuberculosis (Manca et al, 1999), Campylobacter jejuni (Day et al, 2000) and Helicobacter pylori (Basu et al, 2004). In S. aureus, the role of catalase in virulence remains unclear; while some researchers have observed a correlation between virulence and catalase activity (Kanafani & Martin, 1985;Mandell, 1975), others have not found any evidence of this (Cosgrove et al, 2007;Horsburgh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…SODs of Shigella flexneri (Franzon et al, 1990), Salmonella typhimurium (Fang et al, 1999), Listeria monocytogenes (Welch et al, 1979), Aeromonas salmonicida (Barnes et al, 1996) and Photobacterium damselae (Barnes et al, 1999) have been reported to increase the resistance to killing by oxygen radicals. Catalase activity is thought to protect Staphylococcus aureus (Mandell, 1975), and to a limited extent Shigella flexneri (Franzon et al, 1990), Salmonella typhimurium (Tsolis et al, 1995), Mycobacterium tuberculosis (Manca et al, 1999) and Agrobacterium tumefaciens (Xiu & Pan, 2000).…”
Section: Introductionmentioning
confidence: 99%